Caracterización de los residuos sólidos de la ciudad de San Martín de Alao - Guerrero Geraldo, Oscar (2011)
The present research was conducted in the city of San Martin de Alao , El Dorado County , San Martín Department . Alao San Martín is located in the central part of the San Martín Region in the province ofEl Dorado in the high forest land. Its area is 562.57 km2, ranking second extension in the region ofSan Martin. The District of San Martin de Alao has a tropical climate the temperature varies between 28 o and 33 o heat and 18 o and 28 o ofrelative humidity. Under this scenario, this paper entitled "Characterization of Salid Waste ofthe City of San Martin de Alao - 2011 " is the result of an investigation and determination of the physical characteristics ofthe salid waste generated in the city of San Martin Alao . It covers tapies per - capita generation , density, physical composition , humidity and volume of so lid waste from different sources ( domestic, foreign trades , Institutional markets and flea markets ) . The research is supplemented by a survey of the habits and attitudes of users of existing municipal system. On the basis of this information presents a series of conclusions, it makes several recommendations . Even when you know that every municipality in the country has its own reality , the present study is a methodological example can serve as a guide in conducting similar studies anywhere in the country. The characterization of so lid waste from the city of San Martin de Alao , has allowed us to conclude that the total volume ofsolid waste generated in the city is 4.95 m3/day, which is recommended to begin the development an environmental management plan for salid waste that includes design collection routes , environmental education and awareness , closing the dump existing location of a suitable place to dispose salid waste ( landfill , processing plant so lid waste)